Biosynthetic optical waveguide interface integration using biomimetic - de novo design ELP for optoelectronic applications - Seisto, Anni; Hokkanen, Ari; Damlin, Pia; Pylkkänen, Robert; Kiiveri, Kirsi; Borisova, Anna S.; Kvarnström, Carita; Cheng, Xu; Sun, Zhipei; Nonappa; Mohammadi, Pezhman (Elsevier BV, 2026)
The integration of biologically inspired materials into photonic device fabrication offers a promising route toward sustainable and biocompatible alternative to conventional in inorganic or petroleum based synthetic materials used in optoelectronic systems. In this work, we present a biosynthetic approach for waveguide fabrication utilizing a biomimetic - de novo designed elastin-like polypeptide (ELP) formulated into an all-water-based photoresist compatible with two-photon polymerization (2PP). The ELP was genetically engineered and recombinantly produced in microbes for enhanced molecular stability, a critical feature for withstanding both localized and bulk temperature increases that occur during high-intensity laser exposure during printing. The resulting ELP formulation supported direct writing of waveguide architecture without the need for organic solvents, harsh processing steps, or post-functionalization. This aqueous resist formulation exhibits high stability during printing and retains its structural integrity upon curing, making it a promising candidate for environmentally friendly, soft-material photonics. This work establishes a foundation for using biosynthetic polypeptides in the fabrication of functional photonic elements and demonstrates a step toward greener, protein-based optoelectronic manufacturing technologies.